A series of floods in the amur river basin: formation analysis and mechanisms of international cooperation - Andrei V. Shalikovsky (Водное хозяйство России: проблемы, технологии, управление)
In recent years, an outstanding series of fl oods has been observed on the Amur River, diff ering in the conditions for the formation and passage of fl oods, but of these, only the situation of 2013 has been widely covered in scientific publications. Th e forecast of fl oods and the implementation of measures to pass them is complicated by the fact that the river basin is transboundary – 100, 70 and 30% of the catchment areas of the Songhua, Argun and Ussuri rivers are located in China. Therefore, the analysis of the conditions for the formation of extreme floods and the mechanisms of international cooperation to prevent fl oods in the Amur basin is an urgent task.